Unconventional monetary policies and bank credit in the Eurozone: An events study approach - Martins, L. F. (2022)
We study the impact of the unconventional monetary policies implemented by the ECB on bank credit to Eurozone general governments and to households. The database is a macro panel of the 19 Eurozone countries over the period between January 2008 and May 2016. Using an events study approach, we create two dummy variables that reflect the timing and changes of unconventional and conventional monetary policy measures, which we use as key determinants in panel regression models. Our results suggest that unconventional monetary policies have a positive lagged impact on bank credit, with much more to general governments (1.2% per month) than to household consumers (0.2%). All other variables in the models, such as the interest rates, the Industrial Production Index, and the inflation rate have the expected estimated signs. Finally, we estimate the unobserved country-specific fixed effects measured in terms of credit growth rates. The monthly growth rates of loans to households in Ireland are about 0.74% below the average country, which is closely related to its post-2008 banking crisis. Moreover, the net purchases' impact under the Public Sector Purchase Program (PSPP) of loans of Monetary Financial Institutions (MFIs) to general governments was much larger for countries that were hit by the financial and economic crisis.